PEMBUATAN “FRUIT LEATHER” BUAH JERUK MANIS (Citrussinensis L.)DENGAN PENAMBAHAN DAMI NANGKA (Artocarpus heterophyllus) - Sarah Siska Hasibuan; Noviar Harun; Akhyar Ali (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The Purpose of this research is to find the best treatment from the production of sweet orange and jackfruit combination Fruit Leather. This research using Completely Randomized Design with 4 treatment and 4 repetition. This treatment are combining 85 grams sweet orange mush and 15 grams jackfruit (JD1); 65 grams sweet orange mush and 35 grams jackfruit (JD2); 45 grams sweet oranges mush and 55 grams jackfruit (JD3); 25 grams sweet oranges mush and 75 grams jackfruit (JD4). This research using Analysis of Variace (ANOVA) and Duncan’s New Multiple Range Test (DNMRT) with significance level (α) 5%. The result of this research refers that there is a significance differences of each treatment towards Water Content, Acidic Properties (pH), Ash Content, Pectin Content, Sugar Reduction and Organoleptic Test. This research conclude that the best treatment according to Proksimate and Hedonic test is fruit leather product made by combination of 45 grams sweet oranges mush and 55 grams jackfruit mush (JD3) which have Water Content 14.612%, Acidic Properties (pH) 4.87, Ash Content 0.773%, Pectin Content 2.409%, Sugar Reduction 47.637%, And according to Hedonic test for Colour, Taste, Aromatic, Texture Atribute, and whole rating of Fruit Leather liked by Panelis. Key words : sweet orange, fruit leather, jackfruit.